Pengaruh Motivasi Terhadap Kinerja Karyawan Pada DPD Askonas Provinsi Sumatera Selatan - Imam Suroso; Muhammad Deni; Tutik Pebrianti; Aras Tulip; Vivin Afini (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2021)
The aims of this study were to determine the effects motivation on employee performance of DPD Askonas South Sumatera Province. This research was associative quantitative. The data collection method used was the quantitative descriptive analysis. Respondents in this study were all employees DPD Askonas South Sumatera Province of i.e. 40 employees. The data collection tool used in this study was a questionnaire. The data were analysed using SPSS. The conclusions that can be drawn from this study were motivation no significant effect on employee performance of DPD Askonas South Sumatera Province. This shows that the tcount value of the motivation variable is 1.937 while the t-table value is 2.024. In addition, the significance value of 0.060 is greater than the alpha value of 0.05.